2017
DOI: 10.1080/07391102.2017.1364670
|View full text |Cite
|
Sign up to set email alerts
|

Solvent sensitivity of protein aggregation in Cu, Zn superoxide dismutase: a molecular dynamics simulation study

Abstract: Misfolding and aggregation of Cu, Zn Superoxide Dismutase (SOD1) is often found in amyotrophic lateral sclerosis (ALS) patients. The central apo SOD1 barrel was involved in protein maturation and pathological aggregation in ALS. In this work, we employed atomistic molecular dynamics (MD) simulations to study the conformational dynamics of SOD1 monomer in different concentrations of trifluoroethanol (TFE). We find concentration dependence unusual structural and dynamical features, characterized by the local unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…However, a slight decrease in Nc of NTD was observed during the simulation. Thus, to accelerate the unfolding process of NTD, the all-atom MD simulations in the presence of 8 M DMSO for 500 ns were carried out with higher temperatures, very similar to our previous studies (Prakash et al, 2018a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a slight decrease in Nc of NTD was observed during the simulation. Thus, to accelerate the unfolding process of NTD, the all-atom MD simulations in the presence of 8 M DMSO for 500 ns were carried out with higher temperatures, very similar to our previous studies (Prakash et al, 2018a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…This 37-residue construct is similar to Munoz construct with broad unfolding temperatures ranging from 295 to 335 K . Recently, similar unfolding experiments were carried out to study the effect of temperature and denaturants such as trifluoroethanol (TFE) on the unfolding and conformational stability, flexibility, and dynamics of N-terminal domain of TAR DNA-binding protein-43 (TDP-43), Cu/Zn superoxide dismutase (SOD1), and RNA recognition motifs (RRMs) of TDP-43 . These studies revealed the conformational heterogeneity within the structures related to the distinct structural stabilities and unfolding dynamics of these proteins and shed light on the misfolding and aggregation of these proteins.…”
Section: Introductionmentioning
confidence: 98%
“…In humans, the coexistence of several pathologies is driven by the multipolar effects of unhealthy or premature aging [12,13]. Neurodegenerative diseases like Alzheimer's, frontotemporal dementia, and Parkinson's are prevalent and occur among the age group of 45-64 [14][15][16] establishing that the continuum of broad neurodegenerative diseases is clinically, pathologically, and mechanistically associated with age with a spectrum of overlapping clinical symptoms [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%